Perancangan Interior Fasilitas Edukasi Hidroponik di Surabaya - Natalia, Cynthia; Kusumarini, Yusita; Poillot, Jean Francois (Intra, 2017)
The increasingly rapid growth of population in urban areas results in an explosion of human population including in Surabaya city. Consequently, fields and farmlands are transformed into buildings. The lack of farmlands in the city instigates the birth of the urban farming concept. Urban farming is a concept that shifts conventional farming into city farming. Hydroponic is one of the urban farming techniques whereby soil is not required for planting.            In Surabaya, there is a facility that supports hydroponic education activities. However, this current facility is not optimally designed for educational purposes. The research questions of this design are: how to transform room organization within an existing building into a hydroponic education facilities,  design the interior of hydroponic education facilities where hydroponic plants can optimally grow in the room,  how to design the interior of an education facility where the room performance will optimize studying and the health of the people within. The design method is adapted from the process of design thinking that was done by Sarah Gibbons, Nielsen Norman Group through steps; empathize, define, ideate, prototype, test and implement.                The result of this design process is to create a programming that is the analysis of activities and room needs in order to obtain suitable room organization for the functions of hydroponic education facilities. The rooms are designed so that hydroponic plants can optimally grow within using climate control system technology that monitors the humidity, temperature, and wind so that visitors can feel comfortable being in the room whilst plants can still live. Hydroponic can be implemented to every room and can function as decoration as well as an education mean in rooms such as seminar and workshop room, so education activities becomes more optimal. The implementation of green interior concept utilizes ecofriendly materials, maximizes natural light and provides good air quality that is healthy of the users within.